Controlling multi-cycle replication of live-attenuated HIV-1 using an unnatural genetic switch - Yuan, Zhe (ACS Synth Biol, 2017)
A safe and effective human immunodeficiency virus type 1 (HIV-1) vaccine is urgently needed, but remains elusive. While HIV-1 live-attenuated vaccine can provide potent protection as demonstrated in rhesus macaque-simian immunodeficiency virus model, the potential pathogenic consequences associated with the uncontrolled virus replication preclude such vaccine from clinical applications. We investigated a novel approach to address this problem by controlling live-attenuated HIV-1 replication through an unnatural genetic switch that was based on the amber suppression strategy. Here we report the construction of all-in-one live-attenuated HIV-1 mutants that contain genomic copy of the amber suppression system. This genetic modification resulted in viruses that were capable of multi-cycle replication in vitro and could be switched on and off using an unnatural amino acid as the cue. This stand-alone, replication-controllable attenuated HIV-1 virus represents an important step towards the generation of a safe and efficacious live-attenuated HIV-1 vaccine. The strategy reported in this work can be adopted for the development of other live-attenuated vaccines.